1997
DOI: 10.1007/bf03161522
|View full text |Cite
|
Sign up to set email alerts
|

Long-term growth trends of baldcypress (Taxodium distichum (L.) Rich.) at Caddo Lake, Texas

Abstract: Abstracf: Caddo Lake. sitnated on the border of northeast Texas a~ld northwest Louisiana, USA is a medium-sized take dominated by stands of batdcypress (Taxodium disrichum). A study of tree growth was initiated at Caddo Lake to address concerns about the health of the baldcypress ecosystem. The lake has been subjected to several dramatic water-level changes uver |he past 200 years, inc!uding waler-tevel stabilization fotlowi~g dam construction in 19t4. To assess the long-term growth trends of baldcypress trees… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…At least two (maximum four) cores were extracted from each tree. The cores were extracted at least 3 m above the ground to avoid the deformed rings in the buttressed base (Young et al 1995;Keeland and Young 1997). Cores were dehydrated at 40°C for approximately 2 weeks, then glued onto wooden holders and sanded with progressively finer sandpaper (100-600 grit; 125-16 μm (Orvis and Grissino-Mayer 2002)) to prepare surfaces for reading.…”
Section: Methodsmentioning
confidence: 99%
“…At least two (maximum four) cores were extracted from each tree. The cores were extracted at least 3 m above the ground to avoid the deformed rings in the buttressed base (Young et al 1995;Keeland and Young 1997). Cores were dehydrated at 40°C for approximately 2 weeks, then glued onto wooden holders and sanded with progressively finer sandpaper (100-600 grit; 125-16 μm (Orvis and Grissino-Mayer 2002)) to prepare surfaces for reading.…”
Section: Methodsmentioning
confidence: 99%
“…Other studies considering the impacts of impoundment on diameter growth and survival of Taxodium have primarily looked at populations of trees upstream of impoundments (Harms et al 1980;Young et al 1995;Keeland and Young 1997). These studies have found conflicting results, in that responses to flood regime change through time and according to pre-conditioning; however, more continuous, deep flooding does seem to have an adverse effect on diameter growth in Taxodium.…”
Section: Discussionmentioning
confidence: 95%
“…Thus, stands of old baldcypress trees in reservoirs do not reflect a preference or requirement for reservoir habitat as might be inferred from presence-absence data alone. Instead, these stands resulted from natural flow conditions prior to reservoir creation that promoted recruitment (Keeland and Young, 1997). While this extreme example is of a tree, similar patterns hold for mobile poikilotherms.…”
Section: Introductionmentioning
confidence: 85%
“…Baldcypress trees (Taxodium distichum) exemplify this problem. This species cannot recruit in the stable hydrologic conditions of southern USA reservoirs (Keeland and Young, 1997). Thus, stands of old baldcypress trees in reservoirs do not reflect a preference or requirement for reservoir habitat as might be inferred from presence-absence data alone.…”
Section: Introductionmentioning
confidence: 98%